CORRELATION BETWEEN PARENTING AND ANXIETY ON HIGHER ACHIEVER STUDENTS - Rini Sugiarti; Erwin Erlangga (Universitas Semarang, 2017)
This research aims at testing empirically correlation between parenting and anxiety on higher achiever students. Hypothesis of the research is that there is correlation between parenting and anxiety on higher achiever students.This qualitative study was population study with subjects as many as 80 higher achiever students. Data were collected using scales, parenting scale and anxiety scale. Data were analyzed using product moment correlation. The result of the study shows that there was significant correlation between parenting and anxiety on higher achiever students with rxy = 0.870 and (p<0.01) thus the hypothesis of this study was accepted.